2017
DOI: 10.1111/jcpt.12584
|View full text |Cite
|
Sign up to set email alerts
|

Pain intensity and pain self-management strategies following discharge after surgery: An Australian prospective observational study

Abstract: SummaryWhat is known and objective: Up to 80% of patients experience acute pain following surgery. This study aimed to improve the current understanding about the strategies individuals use to self-manage pain following discharge after surgery, stratified by pain intensity. Methods What is new and conclusion:A high proportion of patients underused analgesics despite experiencing moderate-severe pain. Although the vast majority of participants reported receiving advice regarding pain self-management, this did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…It showed that patients may still have pain when they were discharged from the hospital after undergoing invasive treatment or surgery, and the incidence of pain at discharge is as high as 46.5%. This result is similar to the Veal et al [7] study. That study showed that although most patients had received recommendations on pain self-management, 47.3% of patients still reported moderate to severe pain after discharge, and it is recommended that individualized pain management is needed to optimize patient pain care.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It showed that patients may still have pain when they were discharged from the hospital after undergoing invasive treatment or surgery, and the incidence of pain at discharge is as high as 46.5%. This result is similar to the Veal et al [7] study. That study showed that although most patients had received recommendations on pain self-management, 47.3% of patients still reported moderate to severe pain after discharge, and it is recommended that individualized pain management is needed to optimize patient pain care.…”
Section: Discussionsupporting
confidence: 92%
“…The lack of proper pain management causes the pain problem to persist until after discharge from hospital. [ 6 , 7 ] The pain can even last for more than 3 months and becomes a newly added chronic pain, which affects the patient's quality of life, employment, and sleep. [ 4 , 8 ] It also causes patients to seek medical treatment repeatedly, which indirectly leads to huge increases in costs to the healthcare system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 , 27 Patients and parents should be knowledgeable about analgesic use and the risk for side effects in the weeks before surgery and their concerns should continuously be addressed thereafter by the same team to avoid them forgetting information and to ensure correct and consistent education. 26 Prescribing antiemetics based on the reason for symptoms and administering prophylactic treatment to patients is frequent. 4 , 28 However, parents and patients may not be comfortable with the consumption of additional medications; therefore, clinicians should also educate patients on nonpharmacological strategies for pain management and side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pain is one of the most common reasons why patients seek treatment at an emergency department, and remains a common problem in the post-operative setting [ 3 – 6 ] . In a recent Australian study, 47% of patients experienced moderate-to-severe pain 1 week after surgery [ 7 ]. Pain is common, but often poorly managed following cancer treatment with an estimated prevalence rate for certain types of cancer from 29% to 57% [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%